Factors associated with non-transmissible diseases among academic and administrative personnel in a Peruvian university - Ochoa-Vigo, Kattia (2022)
Objective: To investigate for factors associated with non-transmissible diseases and demographic and comorbid conditions among academic and administrative personnel at a Peruvian university. Methods: A cross-sectional study was carried-out at a Peruvian university from December 2018 to February 2019 including 150 participants. The Chi square and Fisher’s exact tests were used and odds ratios with 95%CI were calculated, a p value <0,05 was considered statistically significant. Results: 21.3% of participants had one comorbidity; 11.3% were smokers; 25.3% were drinkers; 66.7% consumed vegetables regularly; 82% did not perform physical exercises; 87.3% had dyslipidemia; 10.7% had arterial hypertension; 46.7% were overweight and 27.3% had obesity. Factors associated with arterial hypertension were male sex (OR=3.59, IC 95%: 1.10-11.70), age above 40 years (OR=4.21, IC 95%: 1.15-15.44), married status (OR=3.06, IC 95%: 1.01-9.31) and having an underlying disease (OR=6.21, IC 95%: 2.09-18.36). Factors associated withe obesity were, being male (OR=4.54, IC 95%:1.97-10.46), living outside Barranca (OR=3.12, IC 95%: 1.27-7.68) and having high triglycerides (OR=10.48, IC 95%: 1.37-80.33).Conclusions: Factors associated with non-transmissible diseases were lack of physical exercise, low intake of vegetables and fruits, drinking alcohol and smoking.